2016
DOI: 10.1002/admi.201500632
|View full text |Cite
|
Sign up to set email alerts
|

Robust Nanostructured Silver and Copper Fabrics with Localized Surface Plasmon Resonance Property for Effective Visible Light Induced Reductive Catalysis

Abstract: Inspired by high porosity, absorbency, wettability, and hierarchical ordering on the micrometer and nanometer scale of cotton fabrics, a facile strategy is developed to coat visible light active metal nanostructures of copper and silver on cotton fabric substrates. The fabrication of nanostructured Ag and Cu onto interwoven threads of a cotton fabric by electroless deposition creates metal nanostructures that show a localized surface plasmon resonance (LSPR) effect. The micro/nanoscale hierarchical ordering of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 48 publications
2
37
0
Order By: Relevance
“…The organic semiconductor AgTCNQ, on the other hand, has a narrow bandgap ( Eg = 0.48 eV) with a work function of 5.17 eV, as recently determined through our in‐depth studies on Ag/AgTCNQ interfaces . The metallic Ag sandwiched between these two semiconductors has a work function of 4.7 eV . Our recent study has shown that Ag and AgTCNQ have appropriate band structures to facilitate rapid electron transfer from Ag to AgTCNQ at the Ag/AgTCNQ interface under photoexcitation conditions .…”
Section: Resultssupporting
confidence: 59%
“…The organic semiconductor AgTCNQ, on the other hand, has a narrow bandgap ( Eg = 0.48 eV) with a work function of 5.17 eV, as recently determined through our in‐depth studies on Ag/AgTCNQ interfaces . The metallic Ag sandwiched between these two semiconductors has a work function of 4.7 eV . Our recent study has shown that Ag and AgTCNQ have appropriate band structures to facilitate rapid electron transfer from Ag to AgTCNQ at the Ag/AgTCNQ interface under photoexcitation conditions .…”
Section: Resultssupporting
confidence: 59%
“…The introduction of increasing amounts of water during CuTCNQ synthesis in MeCN consistently improves the catalytic performance of obtained catalysts ( Table 2 ). Metallic Cu is known to be an outstanding catalyst for ferricyanide reduction reaction, and Cu foil took 22.5 min to drive the reaction to 95% completion. This activity of metallic Cu is better than the CuTCNQ catalyst grown using conventional route in 100% MeCN that took 38 min.…”
Section: Resultsmentioning
confidence: 99%
“…Similar to pristine CuTCNQF 4 , the Cu 2p core level spectra obtained from the materials after galvanic replacement with 1 μM, 100 μM and 1 mM Ag + ions show characteristic 2p 3/2 and 2p 1/2 splitting components from the Cu + species (Figure a ‐ ii‐iv). The absence of signatures corresponding to the shake‐up satellites between 940–950 eV suggests that the GR process does not lead to the formation of Cu 2+ species typically seen in CuO or Cu(OH) 2 ,. This observation is different from our previous work where the GR reaction between CuTCNQ and Ag + resulted in the formation of Cu 2+ species, suggesting that the GR process of CuTCNQF 4 with Ag + does not allow the formation of Cu 2+ species.…”
Section: Resultsmentioning
confidence: 99%